2003
DOI: 10.1177/0115426503018006523
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyte Disorders Following Oral Sodium Phosphate Administration for Bowel Cleansing in Elderly Patients

Abstract: Background: Oral sodium phosphate is currently used for colon preparation before colonoscopy or barium enema. Sodium phosphate induces hyperphosphatemia, hypocalcemia, and hypokalemia. Elderly patients are at an increased risk for phosphate intoxication because of decreased glomerular filtration rate, medication use, and systemic and gastrointestinal diseases. We investigated these electrolyte disorders and their correlation with creatinine clearance, coexistent diseases, medications, and functional status. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(78 citation statements)
references
References 17 publications
1
71
0
6
Order By: Relevance
“…In 1972, Hughes originally questioned MBP and concluded that vigorous mechanical bowel preparation is unnecessary. 49 Not only does MBP cause metabolic and electrolyte imbalance, dehydration, abdominal pain/bloating and fatique, [50][51][52][53] but it may actually have detrimental effects on surgical outcome. 54 Multiple RCTs and meta-analyses have been published over the last decade suggesting that it is safe to abandon MBP.…”
Section: Role Of Mechanical Bowel Preparationmentioning
confidence: 99%
“…In 1972, Hughes originally questioned MBP and concluded that vigorous mechanical bowel preparation is unnecessary. 49 Not only does MBP cause metabolic and electrolyte imbalance, dehydration, abdominal pain/bloating and fatique, [50][51][52][53] but it may actually have detrimental effects on surgical outcome. 54 Multiple RCTs and meta-analyses have been published over the last decade suggesting that it is safe to abandon MBP.…”
Section: Role Of Mechanical Bowel Preparationmentioning
confidence: 99%
“…Serum ionized calcium was calculated using the following formula: serum ionized Ca (mg/dl) = serum total Ca (mg/dl) 3 (100% -%serum protein-bound Ca), where %serum protein-bound Ca = 0. (14).…”
Section: Calculation Of Urinary Phosphate Excretion and Renal Tubularmentioning
confidence: 99%
“…But 2(8%) for anastomotic leak and 3(12%) for intra-abdominal abscess from Group B needed re-operation, which was significant statistically. potentially negative side-effects in terms of bacterial translocation 10,11 , electrolyte disturbance 12 and discomfort to patients 12,13 . Despite these drawbacks, mechanical bowel preparation is still commonly practiced in colorectal surgery, without evidence from randomized trials that it decreases complication rates in patients 14 .…”
Section: Discussionmentioning
confidence: 99%